PELINDIAN BIJIH EMAS MENGGUNAKAN TIOSULFAT DENGAN PERBANDINGAN RASIO PADAT-CAIR 1:20 PADA TEMPERATUR 90? PELINDIAN BIJIH EMAS MENGGUNAKAN TIOSULFAT DENGAN PERBANDINGAN RASIO PADAT-CAIR 1:20 PADA TEMPERATUR 90? - syamsul bahtiar; Nuryosi Ismiana (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2023)
Leaching of gold ore using sodium thiosulfate reagent has been successfully carried out. The gold ore used in this study is gold ore from the Pakirum region, West Sumbawa District, West Nusa Tenggara Province. The use of thiosulfate reagent in this gold separation process is due to its very low toxicity level, can extract various types of ores, and provides a high recovery rate and very fast kinetics compared to cyanide. In this study, the leaching process was carried out using a solid-to-liquid ratio of 1:20 at 90? with a particle size of 200 mesh, using thiosulfate reagent concentration of 0.6M with the help of 30% H?O? oxidizing agent. Gold content testing in this study was carried out using the AAS (Atomic Absobtion Spektrophotometer) test, because AAS has a fairly good level of accuracy and precision. The result of this study indicate that the highest gold recovery is 98.27% in leaching time of 6 hours. While the lowest gold yield was 65.51% at the 2 hours leaching time.